2013
DOI: 10.1002/lary.24024
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of laryngopharyngeal sensation in children with dysphagia

Abstract: The majority of children with dysphagia have impaired LPST. The prevalence of abnormal swallowing function parameters in children with normal LPST is lower than that in children with moderately or severely impaired LPST. Prevalence of aspiration tends to increase when the abnormal swallowing function parameters are associated with severely impaired LPST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 18 publications
1
27
0
2
Order By: Relevance
“…As globus is often treated as reflux disease or a somatoform disorder, further evidence linking sensory loss and globus sensation may change globus management . Also, a patient's risk of dysphagia and aspiration may be directly related to the degree of laryngeal sensory loss, as observed in these cases and previously studied in larger cohorts . Testing laryngeal sensation may be useful to predict risk of aspiration pneumonia, although more evidence is needed to definitively support this.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…As globus is often treated as reflux disease or a somatoform disorder, further evidence linking sensory loss and globus sensation may change globus management . Also, a patient's risk of dysphagia and aspiration may be directly related to the degree of laryngeal sensory loss, as observed in these cases and previously studied in larger cohorts . Testing laryngeal sensation may be useful to predict risk of aspiration pneumonia, although more evidence is needed to definitively support this.…”
Section: Discussionmentioning
confidence: 81%
“…26 Also, a patient's risk of dysphagia and aspiration may be directly related to the degree of laryngeal sensory loss, as observed in these cases and previously studied in larger cohorts. 11,[27][28][29] Testing laryngeal sensation may be useful to predict risk of aspiration pneumonia, 10,29,30 although more evidence is needed to definitively support this.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that laryngopharyngeal sensation is reduced or inhibiting in pediatric and adult patients with OPD. 11 The stimulation of the swallow center in the medulla inhibits the adjacent respiratory center that results in a temporary cessation of respiration, which accompanies the laryngeal upward movement, the closure of epiglottis, and the reflex closure of the larynx during the process of deglutition. The temporal coordination of breathing and pharyngeal phase of swallow is critical.…”
mentioning
confidence: 99%
“…Its suggested use is as a non-radioactive alternative to the modified barium swallow study. Reference [10] used FEESST to assess laryngopharyngeal sensory threshold (LPST) which refers to the intensity of an air pulse stimulus required to trigger laryngeal adductor reflex. Their study showed a significant correlation between LPST impairment and functional impairment.…”
Section: Endoscopymentioning
confidence: 99%